Two new species of Hydraena Kugelann, 1794 from São Tomé Island—an apparent adaptive radiation (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2023)
Hydraena saotometerrestris sp. nov. and H. turneri sp. nov. are described from São Tomé island in the Gulf of Guinea. Both species belong to the subgenus Hydraenopsis Janssens, 1972 and were collected from primary forest locations; H. turneri sp. nov. found living aquatically in a small seepage over rock and clay. In contrast, H. saotometerrestris sp. nov. was collected from damp forest litter, far from water, in two mountainous locations on São Tomé and is apparently terrestrial. The overall habitus and similar form of aedeagus in the new species strongly suggest they are closely related, pointing to apparent adaptive radiation following a single colonization of this oceanic island.